(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In article problems of modeling of pedagogical situations on occupations are considered at said pedowial disciplines. It is shown importance of use of modeling of professional situations in educational P cess of the higher school. It is proved efficiency of modeling of professional situations at studying pedagogics disciplines.